Open science and its enemies: Challenges for a sustainable science-society social contract - Venni V. Krishna (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Science as a social institution has evolved as the most powerful, highly influential, and sought out institution after the conflicts between science and religion following Galileo. Knowledge as a public good, scientific peer review of science, the prominence of open publications, and the emphasis on professional recognition and scientific autonomy have been the hallmark of science in the past three centuries. According to this scientific spirit, the scientific social system and society formed a unique social contract. This social contract drew considerable institutional and state legitimacy for the openness and public good of science in the service of state and society, all through the post-war period. Openness and public good of science are recognized and legitimized by the scientific community and science agencies at the global level. This paradigm of open science, in varying forms and manifestations, contributed to the progress of systematic knowledge at the service of humankind over the last three centuries. Entering the third decade of the 21st century, the social contract between science and society is undergoing major changes. In fact, the whole paradigm of open science and its social contract is being challenged by various "enemies" or adversaries such as (a) market-based privatized commercial science, (b) industry 4.0 advanced technologies, and (c) a "new iron curtain" on the free flow of science data and information. What is at stake? Are there major changes? Is the very social institution of science transforming? What impact will this have on our contemporary and future sustainable society? These are some important issues that will be addressed in this article.
Keywords: 650; ethos of science; industry 4.0; open science; platform capitalism in science; science and society social contract